The Concept and Implementation of Al-Tawaqquf in Mukhtalif Al-Hadith - Razak, Mohd Solleh Ab; Shamsudin, Roshimah (European Publisher, 2019)
Mukhtalif al-Hadith, which is the application of al-Tawaqquf methods by the mujtahid for interacting with acceptable (maqbul) hadiths, often raises more questions than answers. More specifically is the case in the implementation of the above method wherein the mujtahids were unable to get two hadiths incongruent over a particular issue, whereas there could never be contradictions amongst the hadiths. This paper examines the concept and application of al-Tawaqquf in Mukhtalif al-Hadith according to hadith scholars. The research is conducted via data collection methods sourced from literature review. Data from various major hadith compilations and the Ulum al-Hadith are analyzed based on deductive and inductive methods. The findings show that the al-Tawaqquf concept is based on several principles. Applying it becomes compulsory in the event of failure to resolve inconsistencies among hadiths. In those situations the mujtahid and his inability is blamed, and this does not absolve other mujtahids from continuing their efforts. This research also proves that the al-Tawaqquf methodology is not only one solution to solve the discrepancies amongst hadiths but is one of the methods engaged by hadith jurists when they cannot reconcile contradictions.